A RANDOMIZED CONTROLLED TRIAL OF CURCUMIN AND DICLOFENAC COMBINATION IN KNEE OSTEOARTHRITIS - SHEP, DHANESHWAR; KHANWELKAR, CHITRA; GADE, PRAKASHCHANDRA; KARAD, SATYANAND (International Journal of Current Pharmaceutical Research, 2019)
Objective: The objective of the study was to evaluate pain relief and safety of the combination of curcumin and diclofenac versus diclofenac alone in the treatment of knee osteoarthritis (OA). Methods: 140 patients of knee OA meeting inclusion criteria were randomized to receive either curcumin 500 mg with diclofenac 50 mg twice daily or diclofenac 50 mg tablet alone twice daily for 28 d. Patients were assessed at baseline, Day 14 and Day 28. Primary efficacy measure was severity of pain (Visual Analogue Scale) at day 14 and day 28. Safety after treatment was evaluated by recording side effects and laboratory investigations. Results: Patients receiving curcumin plus diclofenac showed significantly superior improvement in severity of pain at each study visit (p<0.001) when compared to diclofenac. Adverse effects were significantly less in curcumin plus diclofenac group (p<0.001). Conclusion: Combination of curcumin and diclofenac showed a significant improvement in pain on the basis of VAS when compared to diclofenac which may be due to synergistic effect between curcumin and diclofenac